تصميم مشروع حضري سياحي مستدام بمدينة الشارف - جبايلي, أحمد; Saci, Mohamed, Directeur de thèse (My University, 2020)
This work is part of a sustainable urban tourism project in the town of Charef (District of Djelfa) with its thermal bath. This work includes a theoretical part to explain the technical terms contained in the subject as well as the study of two examples similar to our project. The second part consists in the urban analysis carried out according to the SWOT method which gives a dynamic vision of the city. In the third part of the project we developed an urban project adapted to the specificities of the city. This project aims at suggesting an alternative to the structural architecture which has shown its limits since the end of the last century. The aim of this project is to make the town of Charef attractive in a sustainable tourist environment for better comfort for tourists
Laghouat : Université Amar Telidji - Département d'architecture Option : urbanisme